Establishment and development of rules of ethical behavior of employees of internal affairs bodies - Masyuk , Lesya (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
Summarizing the above retrospective analysis of the formation and development of the rules of ethical behavior of employees of the OVS, we can distinguish specific stages of their development: The first stage is optional, since during this period the works of famous philosophers on moral and ethical teachings, which became the basis for the formation of future moral principles, began to appear and ethics of public servants; The II stage covers the formation of the Russian state, in that period the main legal acts were Russian truth, Lithuanian statutes, and Council regulations, which also determined the moral principles of public activity, but did not contain specific prescriptions of an ethical nature; Stage III, the period when the Ukrainian lands were under the rule of Austria, Austria-Hungary and the Russian Empire, during this period of time there was an understanding of the need to establish the moral and ethical requirements of public servants, in particular police officers, at the regulatory and legal level; The 4th stage plays a special role in the formation of moral and ethical values of employees of the OVS, since from this period such terms as discipline, legality, moral and ethical requirements, official reputation appear in the relevant normative legal acts; The fifth stage of the Soviet era, in which the Soviet militia was created, and the moral and ethical aspects of its activity were regulated in sufficient detail by a separate normative act; The VI stage is associated with Ukraine gaining independence and expanding the regulatory base of moral and ethical rules for employees of the Ukrainian Armed Forces; Stage VII - the creation of the National Police of Ukraine, which necessitated the formation of police legislation, including those laws and by-laws that regulated ethical issues of service in police bodies, in particular the Law of Ukraine «On the Disciplinary Statute of the National Police of Ukraine» and the Rules of Ethical Conduct police officers, approved by the order of the Ministry of Internal Affairs of Ukraine dated November 9, 2016 No. 1179, respectively.